PEMANFAATAN HCl dan CaCl2 SEBAGAI ZAT AKTIVATOR DALAM PENGOLAHAN LIMBAH INDUSTRI TAHU - Hatina, Surya; Komala, Ria; Wahyudi, Randa (Politeknik Negeri Sriwijaya, 2019)
The purpose of this research is to determine the effectiveness of activated carbon from bagasse with activator subtances HCl and CaCl2 in reducing the parameters of COD and TSS and increasing the DO and PH parameters in the tofu processing waste. The optimum conditions in reducing the COD and TSS parameters and increasing the DO and PH parameters in the tofu processing waste are 12 hours of circulation time with a fixed bed reactor. The results of the study with the use of 0.3 M HCl activator has a better ability than 0.2 M CaCl in reducing COD and TSS values and increasing DO and PH values.The results ofusing activator substances HCL 0.3 M has a better ability than 0.2 M CaCl in reducing COD and TSS values and increasing DO and PH values. The decrease in COD value from 123.7 mg / L to 41.6 mg / L or 66.37%, a decrease in TSS value from 335 mg / L to 103.8 mg / L or 69.1%, an increase in DO value from 1.86 mg / L to 7.6 mg / L or 75.52%, and the increase in pH value from 3.53 to 4.66.